Outdoor weathering of polyamide and polyester ropes used in fall arrest equipment. Issue 5 (8th June 2013) - Arrieta, Carlos; Dong, Yingying; Lan, André; Vu‐Khanh, Toan
ABSTRACT In this work, the effect of natural climatic aging on two ropes made from polyamide 6 (PA6) and poly(ethylene terephthalate) (PET) was evaluated. Samples of rope from both materials underwent a continuous outdoor aging treatment spanning 6 months in Montreal's weather. Tensile tests carried out on aged PA6 ropes showed an increase in ultimate strain and a decrease in breaking force when compared with as‐received values, while PET ropes exhibited a slight increase in ultimate strain as their breaking force remained unchanged. FTIR analyses of aged PET samples revealed a new absorption band in the hydroxyl region ascribed to the OH stretching vibrations of carboxylic acid end groups. FTIR quantitative analyses of the absorption bands in the carbonyl region of aged PA6 spectra displayed an increase in intensity that indicates the occurrence of chemical degradation reactions. The degree of crystallinity of PA6, calculated from differential scanning calorimetry data, was found to increase after the weathering treatment, a result confirmed by X‐ray diffraction analyses. The higher crystalline fraction is believed to entail an increase in the density of PA6 fibers, which give rise to the length reduction seen in PA6 ropes after the aging treatment. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 3058–3065, 2013